Effect of hemolysis on Fourier transform infrared and Raman spectra of blood plasma. Issue 7 (7th April 2020) - Medipally, Dinesh K. R.; Cullen, Daniel; Untereiner, Valérie; Bryant, Jane; Sockalingum, Ganesh D.; Nguyen, Thi N. Q.; Noone, Emma; Bradshaw, Shirley; Finn, Marie; Dunne, Mary; Shannon, Aoife M.; Armstrong, John; et al.
Abstract: Hemolysis is a very common phenomenon and is referred as the release of intracellular components from red blood cells to the extracellular fluid. Hemolyzed samples are often rejected in clinics due to the interference of hemoglobin and intracellular components in laboratory measurements. Plasma and serum based vibrational spectroscopy studies are extensively applied to generate spectral biomarkers for various diseases. However, no studies have reported the effect of hemolysis in blood based vibrational spectroscopy studies. This study was undertaken to evaluate the effect of hemolysis on infrared and Raman spectra of blood plasma. In this study, prostate cancer plasma samples (n = 30) were divided into three groups (nonhemolyzed, mildly hemolyzed, and moderately hemolyzed) based on the degree of hemolysis and FTIR and Raman spectra were recorded using high throughput (HT)‐FTIR and HT‐Raman spectroscopy. Discrimination was observed between the infrared and Raman spectra of nonhemolyzed and hemolyzed plasma samples using principal component analysis. A classical least square fitting analysis showed differences in the weighting of pure components in nonhemolyzed and hemolyzed plasma samples. Therefore, it is worth to consider the changes in spectral features due to hemolysis when comparing the results within and between experiments. Abstract : Hemolysis interferes with various laboratory tests. Despite being very common in practice, no spectroscopic study has examined the effects of hemolysis on spectral markers and the concentration of analytes. This study reports significant changes in the Raman and FTIR spectra of blood plasma due to in vitro and in vivo hemolysis. Therefore, it is worthwhile to consider the changes in spectral features due to hemolysis when comparing the results within and between experiments.